The effectiveness of the combined treatment package based on acceptance and commitment and positive treatment and on the control of emotions and perseverance of female managers - Soheil Mirsadeghi, Seyed Ali; Borjali, Ahmad; Sadeghi, Meysam (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The present study was conducted with the aim of investigating the effectiveness of the combined therapy package based on acceptance and commitment and positive therapy on emotional control and perseverance of female managers. Methods: The research method was a quasi-experimental pre-test-post-test type with a control group with a follow-up period of two months. The statistical population of the research included all female managers of Bahar Zeit, Barsa and Hamon Naizeh institutions and organizations in 2021. The selection of samples was available in the form of sampling method and the sample size in this section was also based on the type of research in two groups of 32 people. The research tools included Duckworth et al.'s persistence questionnaire (2007), and Williams et al.'s (1997) emotion control scale. The results of the qualitative part of the research led to the development of an 18-session combined therapy package based on acceptance and commitment and researcher-made positivity. Data analysis was done with SPSS version 16 software and analysis of variance test with repeated measurement between groups at a significance level of α=0.05. Results: The results of data analysis showed that the combined treatment method of acceptance and commitment and positivity on anger control scores (F=7.72, P=0.010), depressed mood control (F=20.37, P=0.001), anxiety control (F=4.31, P=0.040), perseverance and self-efficacy (F=3.96, P=0.040), and this effect is also in the follow-up stage compared to the pre-test. It was meaningful. Conclusion: Considering that the combined training of positive psychology and the psychology of acceptance and commitment increased the control of emotions (anger, anxiety, depression and positive emotions) and the perseverance of managers, it is suggested that organizations and companies, both in the private and public sectors, Use this training and treatment package intervention for their organizational growth and improvement.